التنمية البيئية المستدمة دراسة تحليلية في ضوء مقاربة الحكم الراشد دراسة حالة ظاهرة التصحر بالجزائر - نجيب, أحمدي (جامعة الوادي University of Eloued, 2017)
تزايد الإهتمام بموضوع البيئة في العقود الأخيرة سواء على المستوى الداخلي للدول أو على مستوى العلاقات الدولية ، ويتجلى ذلك بوضوح في تطور المنظومات التشريعية المنظمة لقضايا لبيئة وتوسع الوعي بمخاطر المساس بالتوازن البيئي ، إن إستمرار التدهور البيئي وما صاحبه من إنعكاسات سلبية على الإنسان و الطبيعة ، ثم بروز التناقض الواضح في مفهوم العلاقة بين التنمية والبيئة جعل البعض يرى بأنهما شيئان متناقضان ، وبالتالي جب إختيار أحدهما عن الآخر في حين يرى البعض عكس ذلك ، ذلك لأن التنمية والبيئة عنصران مرتبطان ارتباطا وثيقا ، و ان فرص تحقيق التنمية لا تتسع و لا يمكن لها أن تستمر إلا إذا تم التركيز على الإستغلال الرشيد و العقلاني لمعطيات الأنظمة البيئية ، تعرف البيئة إصطلاحا بأنها الوسط الطبيعي الذي يعيش فيه الإنسان و الكائنات الحية الأخرى ويمارس فيها نشاطاته المختلفة الإنتاجية و الإجتماعية . وكانت اشكالية كالآتي : إلى أي مدى يمكن القول أن التنمية البيئية تساهم في تحقيق التنمية المستدامة ؟ وما هي أهم الآليات المتبعة في مكافحة ظاهرة التصحر، وهل هناك فعالية للآليات المستخدمة من قبل الجهات الرسمية ؟ . و قمت في هذه المذكرة بالتطرق في الفصل الاول للإطار النظري من حيث مفهوم التنمية البيئية المستدامة ، وكذا المفاهيم والمقاربات المتعلقة بها وبالضبط في المبحث الأول قمنا بإعطاء مفهوم عن التنمية البيئية بكل عناصرها وجوانبها، وكذلك تطرقنا في المبحث الثاني لأهم المقاربات النظرية في التنمية البيئية ، ثم تناولنا في المبحث الثالث مؤشرات التنمية البيئية ، أما في الفصل الثاني والذي حمل عنوان السياسات الجزائرية المتعلقة بالتنمية المستدامة دراسة لظاهرة التصحر فتطرقنا في المبحث الأول إلى مفهوم ظاهرة التصحر وكذلك أسبابه و أهم آثاره الإقتصادية و الإجتماعية ثم تطرقنا في المبحث الثاني إلى الآليات المستعملة من طرف الجزائر في مجال مكافحة ظاهرة التصحر وحماية البيئة ، ثم في المبحث الثالث تناولنا مستقبل البيئة في الجزائر Growing interest in the topic of the environment in recent decades, both at the domestic level to the states or at the level of international relations, and this is reflected clearly in the evolution of the legislative systems of the Organization to the issues of environment and expand awareness of the risks compromising the ecological balance, that the continued environmental degradation coupled with the negative impact on man and nature, and then the emergence of the apparent contradiction in the concept of the relationship between development and the environment led some to believe that they are two things contradictory, and therefore Jeb choose from one another, while some see the opposite, because the development environment elements are inextricably linked, and that the chances of achieving development can not be accommodated and it can not be continue unless the focus on the rational exploitation of the data and rational environmental regulations, environmental idiomatically known as the natural environment in which man lives and other organisms and practiced various activities and social productivity. The problematic as follows: to what extent it can be said that environmental development contribute to the achievement of sustainable development? What are the most important mechanisms used in the fight against desertification, and whether there are effective mechanisms used by official bodies? . And in this note addressing in the first chapter the theoretical framework in terms of the concept of sustainable environmental development, as well as the concepts and approaches related and exactly in the first part, we have to give the concept of environmental development in all its elements and its aspects, as well as we discussed in the second section of the main approaches to theory in environmental development, and we dealt with in the third section of environmental development indicators, while in the second quarter and that carried the Algerian policies for sustainable development study of the phenomenon of desertification title Vttrguena in the first section to the concept of the phenomenon of desertification, as well as its causes and the most important economic effects and social and then we touched in the second section to the mechanisms used by Algeria in the field of combating desertification and protecting the environment, and then in the third section we dealt with the future of the environment in Algeria
انظمة سياسية مقارنة والحكم الراشد
Keywords: البيئة- التنمية البيئية المستدامة- التصحر- السد الأخضر- الرشادة البيئية; Environment Agency and Environmental Development, Desertification Almstdamh- dam green- environmental rationalization